PEMBELAJARAN MATEMATIKA SMP DALAM PERSPEKTIF LANDASAN FILSAFAT KONSTRUKTIVISME - Permata, Laelatul Dhian; Rahmawati, Dinda; Fitriana, Laila (Jurnal Pembelajaran Matematika, 2018)
Abstract: Constructivism is one of the views in learning theories that affect much of the learning of mathematics. According to experts, the view of mathematics learning as discovery and construction by students is better than the abstract set of science informed by the teacher. Junior high school students are students who begin to be introduced and understand abstract way of thinking, so students should not be taught by way of rote memorization without meaning, especially on learning mathematics filled with abstract symbols. This article aims to describe the learning of Junior high school mathematics in constructivism perspective: planning, process, assessment of learning, role of student and teacher role. This article is using library research method. The data collected and analyzed are secondary data in the form of research results including books, journal articles and conference proccedings relevant to the topic. The results show that constructivism is a new way of thinking that knowledge is not only through the transfer process, but the knowledge grows and develops from activities, such as the activity of constructing the concept of variables and constants using the help of contextual problems. Assessment used in learning mathematics in the perspective of constructivism is formative and summative assessment. The role of students in junior mathematics learning with constructivism approach focuses on student activity in constructing their own knowledge and its consequences. Meanwhile, the role of teachers in junior high school mathematics with constructivism approach is divided into two namely the teacher as a facilitator and moderator.Keywords: Teacher, Constructivism, Mathematics Learning, Student